Detection and monitoring of lung inflammation in cystic fibrosis during respiratory tract exacerbation using diffusion-weighted magnetic resonance imaging. Issue 1 (20th July 2017) - Ciet, Pierluigi; Bertolo, Silvia; Ros, Mirco; Andrinopoulou, Eleni Rosalina; Tavano, Valentina; Lucca, Francesca; Feiweier, Thorsten; Krestin, Gabriel P.; Tiddens, Harm A.W.M.; Morana, Giovanni
The aim was to investigate whether diffusion-weighted magnetic resonance imaging (DWI) detects and monitors inflammatory and lung function changes during respiratory tract exacerbations (RTE) treatment in patients with cystic fibrosis (CF). 29 patients with RTE underwent DWI pre- and post-antibiotic treatment. A control group of 27 stable patients, matched for age and sex, underwent DWI with the same time gap as those undergoing RTE treatment. Clinical status and lung function were assessed at each DWI time point. The CF-MRI scoring system was used to assess structural lung changes in both CF groups. Significant reduction in the DWI score over the course of antibiotic treatment (p<0.0001) was observed in patients with RTE, but not in the control group. DWI score had a strong inverse correlation with clinical status (r=−0.504, p<0.0001) and lung function (r=−0.635, p<0.0001) in patients with RTE. Interestingly, there were persistent significant differences in the CF-MRI score between the RTE and control group at both baseline and follow-up (p<0.001), while the differences in DWI score were only observed at baseline (p<0.001). DWI is a promising imaging method for noninvasive detection of pulmonary inflammation during RTE, and may be used to monitor treatment efficacy of anti-inflammatory treatment. DWI is a promising imaging method to detect and monitor the severity of inflammation during RTE in CF patients http://ow.ly/Ulcc30c0ebU